(untitled) (The Review of Diabetic Studies, 2024)
Background: Sepsis represents a dysregulated host response to infection associated with life-threatening organ dysfunction. It remains a leading cause of global mortality and a significant burden on healthcare systems. The heterogeneity of clinical presentation necessitates a multimodal diagnostic approach. While the "Golden Hour" of sepsis management emphasizes rapid recognition and intervention, reliance on single-modality screening tools often leads to missed diagnoses or alarm fatigue. Objective: This systematic review aims to evaluate the diagnostic accuracy, prognostic value, and clinical utility of correlating nursing clinical indicators (specifically capillary refill time, qSOFA, and early warning scores) with rapid laboratory biomarkers (lactate, procalcitonin, emerging markers) and radiologic imaging (Point-of-Care Ultrasound, Chest X-ray). Furthermore, it assesses the impact of multidisciplinary Sepsis Emergency Response Teams (SERTs) on patient outcomes and protocol compliance. Methods: A systematic literature search was conducted encompassing studies published through 2023. Included studies were assessed for risk of bias using Cochrane RoB 2 for randomized trials and QUADAS-2 for diagnostic accuracy studies. Data regarding sensitivity, specificity, and Area Under the Receiver Operating Characteristic (AUROC) curve were synthesized to evaluate the performance of individual and combined diagnostic modalities. Results: Analysis reveals that no single marker possesses perfect diagnostic utility. Nursing indicators such as qSOFA demonstrate high specificity (0.96–0.98) but poor sensitivity (0.29–0.50), making them suitable for risk stratification but inadequate for initial screening compared to SIRS or NEWS. Capillary Refill Time (CRT) serves as a robust real-time indicator of microcirculatory status, often uncoupling from metabolic markers like lactate during resuscitation. Among biomarkers, lactate remains the standard for assessing metabolic stress (AUROC 0.76), while procalcitonin (PCT) offers superior specificity for bacterial etiology (AUROC 0.86) and guides antibiotic stewardship. Radiologic integration, particularly POCUS, significantly improves the differentiation of shock types (Sensitivity 78% for septic shock etiology) compared to standard clinical assessment. Integrated models, such as LqSOFA (Lactate + qSOFA) and nurse-led POCUS-guided fluid protocols, demonstrate superior predictive validity (AUROC >0.81) and improved bundle compliance. Multidisciplinary SERTs utilizing these integrated protocols are associated with significant reductions in mortality and time-to-antibiotics. Conclusion: The management of acute sepsis requires the triangulation of bedside nursing assessment, rapid metabolic profiling, and functional imaging. Moving beyond rigid protocols to physiology-guided, multidisciplinary care models—specifically those empowering nurses with POCUS and standardized biomarker algorithms—represents the most evidence-based strategy for improving survival.